An Expedition on Alkali and Alkaline‐Earth Isocyanurate Hydrates: Structure Elucidation, Thermogravimetry, and Spectroscopy. Issue 21 (14th November 2017) - Gross, Peter; Höppe, Henning A.
Abstract : Several alkali and alkaline earth (iso)cyanurates were synthesized by simple aqueous acid‐base reactions and aqueous salt metathesis reactions, respectively, yielding nine new structure types. Single‐crystals could be grown and the crystal structures of Rb[H2 C3 N3 O3 ]· H2 O‐I, Rb[H2 C3 N3 O3 ]· H2 O‐II, Cs[H2 C3 N3 O3 ]· 0.5H2 O, Sr[H2 C3 N3 O3 ]2 · 4H2 O, Ba3 [H2 C3 N3 O3 ]2 [HC3 N3 O3 ]2 · 4H2 O, Ca[HC3 N3 O3 ]· 3.5H2 O, Sr[HC3 N3 O3 ]· 3H2 O, Sr[HC3 N3 O3 ]· 2H2 O, and Sr2 [C3 N3 O3 ]OH were elucidated by single‐crystal XRD. Rb3 [H2 C3 N3 O3 ]3 [H3 C3 N3 O3 ]· 4H2 O, Cs[H2 C3 N3 O3 ]· 0.5H2 O, and Sr[HC3 N3 O3 ]· 2H2 O were synthesized as phase pure, crystalline powders and were further characterized by powder XRD, FT‐IR spectroscopy, UV/Vis spectroscopy, and thermogravimetry. Sr[HC3 N3 O3 ]· 2H2 O was shown to be an air‐ and water‐resistant, cheap and easily obtained precursor for the phase‐pure synthesis of Sr3 [C3 N3 O3 ]2, a promising SHG material, and Sr[NCN]. Moreover, an interesting dependence of the polymeric anion structure from its protonation degree was observed. Abstract :